Formation and Characterization of Beclomethasone Dipropionate Nanoparticles Using Rapid Expansion of Supercritical Solution - Mohsen Hosseinpour; Alireza Vatanara; Reza Zarghami (Tabriz University of Medical Sciences, 2015)
Purpose: Particle size of Beclometasone Dipropionate (BDP) was reduced by the rapid expansion of supercritical solution (RESS) process, using CO2 as supercritical solvent. Also, the effect of RESS parameters such as extraction pressure, pre-expansion temperature, and weight fraction of co-solvent on the size and distribution of BDP particles were investigated. Methods: The effects of extraction pressure (200-260 bar), pre-expansion temperature (70-110 °C) and weight fraction of menthol as a co-solvent on mean particle size (MPS) of BDP were investigated by design of experiment (DOE). Particles were characterized using Scanning Electron Microscopy (SEM) and Dynamic Light Scattering (DLS). Results: The average sizes of precipitated BDP were between 64.1 and 294 nm. Analysis of variance (ANOVA) showed that extraction pressure was the most significant parameter and a higher extraction pressure caused production of smaller particles. Also, it was found that higher temperature and weight fraction of co-solvent increased the MPS. The interaction effects of extraction pressure-pre-expansion temperature and pre-expansion temperature-co-solvent ratio were significant through the analysis of variance. It was observed that the MPS of precipitated particles was mostly influenced by pressure. Conclusion: The smallest MPS of BDP obtained from the RESS process was 65 nm that revealed a significant size reduction from its original MPS of 9 μm. Moreover, a slight change was observed for precipitated particles of BDP into spherical form while the original particles were irregular in shape. RESS process showed as a promising method for production of BDP nanoparticles that may results in improvement of drug's physicochemical properties.